Seismic performance of new adobe bricks masonry: Design and experiment. Issue 2 (January 2022) - Zhou, Tiegang; Wang, Xin; Ma, Ben; Zhang, Zaiyu; Tan, Wei
At present, adobe houses with traditional characteristics are still widely used in rural areas in western China, but their seismic performance is relatively poor, and they often suffer serious damage under earthquake. To improve the seismic performance of traditional adobe buildings while retaining the characteristics of residential buildings, the mechanical properties of compressed earth blocks (CEB) were tested in this study, and the microstructure characteristics of CEB after failure were analyzed by electron microscope. On this basis, six adobe wall specimens were designed and tested by quasi-static loading to investigate the influence of core columns and different types of bricks on its seismic performance. The results show that the core column can improve the bearing capacity and shear capacity of hollow CEB, and it can also significantly increase the bearing capacity, energy dissipation capacity, and ductility of CEB wall. In general, the adobe wall with core columns shows excellent seismic performance, which can provide a new choice for improving the seismic performance of the adobe house.